2016
DOI: 10.1016/j.jhe.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness prevention in New York City: On average, it works

Abstract: This study evaluates the community impact of the first four years of Homebase, a homelessness prevention program in New York City. Family shelter entries decreased on average in the neighborhoods in which Homebase was operating. Homebase effects appear to be heterogeneous, and so different kinds of averages imply different-sized effects. The (geometric) average decrease in shelter entries was about 5% when census tracts are weighted equally, and 11% when community districts (which are much larger) are weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…For example, Collinson and Reed (2018) found that eviction increased the risk and duration of shelter use among individuals in New York City. Similarly, two studies found that community-level homelessness rates increased with a rise in local area foreclosures (Goodman, Messeri, and O'Flaherty 2016;Faber 2019). However, to our knowledge, there are no quantitative studies investigating the association between forced housing moves and other forms of homelessness such as doubling up.…”
Section: Explanations For Child and Family Homelessnessmentioning
confidence: 95%
“…For example, Collinson and Reed (2018) found that eviction increased the risk and duration of shelter use among individuals in New York City. Similarly, two studies found that community-level homelessness rates increased with a rise in local area foreclosures (Goodman, Messeri, and O'Flaherty 2016;Faber 2019). However, to our knowledge, there are no quantitative studies investigating the association between forced housing moves and other forms of homelessness such as doubling up.…”
Section: Explanations For Child and Family Homelessnessmentioning
confidence: 95%
“…6 If accessing homelessness prevention services is harder, only a selected group of potential participants will do it, and that group will be selected on the basis of private information (and public information) indicating that they are likely to enter homelessness soon. See Goodman et al (2016) for suggestive evidence of a process like this working in New York City.…”
Section: Homelessness Prevention and Program Accessibilitymentioning
confidence: 98%
“…Recent evaluations of homelessness prevention programs in New York City (Rolston et al, 2013, Goodman et al, 2016 and Chicago (Evans et al, 2015) have shown favorable ratios of benefits to costs. These results were not completely anticipated: experts in the early 21 st century generally felt that prevention was not a promising way to combat homelessness (Shinn et al, 2001, Burt et al, 2005.…”
Section: Homelessness Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to families who received services as usual, families referred for homelessness prevention exhibited significant decreases in the probability of shelter seeking as well as days in shelter. Moreover, a quasi-experiment that compared neighbor-hoods served by HomeBase to similar neighborhoods outside of the catchment area showed significantly lower than expected rates of homelessness at the community level (Goodman, Messeri, & O’Flaherty, 2016). Linked child welfare records showed no differences in rates of formal placement into foster care; however, overall placement levels were small among a relatively small group of families referred for HomeBase ( n = 11/150) versus control families ( n = 3/145; Rolston et al, 2013).…”
Section: Policy Initiatives and Emerging Evidence On Housing Intervenmentioning
confidence: 99%